Ontogenetic and other variations in muskoxen, with a systematic review of the muskox group, recent and extinct. Memoirs of the AMNH - Allen, J. A. (Joel Asaph), 1838-1921. ([New York], 1913)
p. 101-226. illus., plates, map. 36 cm. Bibliography: p. 221-226.